Retraction: Effects of Sodium Lighting on Circadian Rhythms in Rats - Chen, Xian (J Am Assoc Lab Anim Sci, 2019)
This retracts the article entitled, “Effects of Sodium Lighting on Circadian Rhythms in Rats” by Xian Chen, Chang-Ning Liu, and Judith E Fenyk-Melody published in the May issue vol 58, issue 3, p 311–320.(1) This article is being retracted with the support of all 3 coauthors due to methodological and authorship issues.